Safe Havens, Feedback Loops, and Shock Propagation in Global Asset Prices - Ohnsorge, Franziska (IMF Working Papers; Working Paper, 2014)
We create a network of bilateral correlations of changes in sovereign bond yields and individual bank equity price changes since 2000. We extract some stylized facts from this network of asset price correlations and document the clear differences in asset price correlations between safe havens and non-safe havens: safe havens, as commonly defined, have higher sovereign-sovereign, bank-bank, and bank-sovereign correlations than nonsafe havens. In a simple shock propagation model, we illustrate how these higher correlations may turn safe havens into shock propagators. While we discuss safe havens as a group, we document how the US is in a category of its own, differing significantly from the other countries including Switzerland or Japan. Separately, we find that feedback loops amplify shocks, and those emanating from bank stress more than those emanating from sovereign stress.